Joint analysis of longitudinal and survival AIDS data with a spatial fraction of longterm survivors: a Bayesian approach - Martins, Rui (2017)
Poster presented at the Joint Modeling and Beyond Workshop, Hasselt University, Belgium, 14-15 April 2016